Analisis Kepuasan Pengguna Learning Management System (LMS) Si-Prestasi menggunakan End User Computing Satisfaction (EUCS) (Studi pada SMP Negeri 1 Pace) - Lulud Mardhiartika Putri; Ismiarta Aknuranda; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Si-Prestasi is an information system that serves to help teachers and students of SMP Negeri 1 Pace in conducting distance learning processes by involving technology. However, there are complaints felt by teachers and students of SMP Negeri 1 Pace in the use of Si-Prestasi such as the inaccurate information generated by the system in displaying scores, frequent disruptions on the server and difficulty for teachers and students in using Si-Prestasi due to the absence of socialization and manuals for the use of Si-Prestasi. During the implementation of Si-Prestasi has never been conducted user satisfaction analysis of Si-Prestasi. The purpose of the study was to describe the factors in End User Computing Satisfaction (EUCS) against Si-Prestasi at SMPN 1 Pace, which consists of variables of content, accuracy, format, ease of use, and timeliness. Data collection using quantitative in the form of dissemination of questionnaires to students and teachers smpn 1 Pace as many as 90 respondents, supported by qualitative data in the form of interviews. The analysis used is descriptive statistical analysis and source triangulation. The results of this study show that most si-prestasi users agree that the content, accuracy, format, ease of use, and timeliness contained in Si-Prestasi are good. However, there are still some users who find it difficult and feel that Si-Prestasi's system is still not good.